2019
DOI: 10.21511/imfi.16(4).2019.16
|View full text |Cite
|
Sign up to set email alerts
|

An application of Altman Z-score model to analyze the bankruptcy risk: cases of multidisciplinary enterprises in Vietnam

Abstract: This study applied Altman Z-score model to assess the bankruptcy risk of a set of multidisciplinary enterprises of various types, mainly small and medium enterprises, with data taken from official financial reports of 180 enterprises in Soc Trang province. The binary logistic regression was employed to assess the impact of non-financial and financial factors on the bankruptcy risk of enterprises. The research findings showed that both the non-financial factors such as business area, types and size of the busin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
1
6
0
4
Order By: Relevance
“…Many studies that deal with Altman's original Z-score model have confirmed that this test is able to significantly differentiate the financial situation between failure companies and nonfailure companies (e.g., Tung et al [85]; Soon et al [86]; Reisz and Perlich [87]; for retail companies-Chaitanya [88] (accuracy of 94%); for nonfinancial services and industry companies-Alkhaib and Bzour [89] (accuracy of 93.8%)). Ashraf et al [90] found that both models by Altman and Zmijewski are decent for bankruptcy for emerging markets when applied in periods of financial crisis.…”
Section: Literature Review On Bankruptcy Prediction Modelsmentioning
confidence: 99%
“…Many studies that deal with Altman's original Z-score model have confirmed that this test is able to significantly differentiate the financial situation between failure companies and nonfailure companies (e.g., Tung et al [85]; Soon et al [86]; Reisz and Perlich [87]; for retail companies-Chaitanya [88] (accuracy of 94%); for nonfinancial services and industry companies-Alkhaib and Bzour [89] (accuracy of 93.8%)). Ashraf et al [90] found that both models by Altman and Zmijewski are decent for bankruptcy for emerging markets when applied in periods of financial crisis.…”
Section: Literature Review On Bankruptcy Prediction Modelsmentioning
confidence: 99%
“…Hanya Menteri Keuangan saja yang dapat melakukan permohonan pailit terhadap perusahaan Asuransi yang kemudian dialihkan kepada Otoritas Jasa Keuangan (untuk selanjutnya disebut Otoritas Jasa Keuangan) sejak diundangkannya Undang-Undang Nomor 21 Tahun 2011 Tentang Otoritas Jasa Keuangan (Tung, 2019).…”
Section: Pendahuluanunclassified
“…Esto ha dado lugar a una gran cantidad de aplicaciones y modificaciones del modelo de Altman Z-Score ya sea para países específicos, empresas privadas o mercados emergentes (Kapounek et al, 2022). Recientemente se han publicado investigaciones sobre la adaptación del modelo de puntaje Z de Altman en sectores específicos de diferentes economías tales como: empresas privadas europeas (Kapounek et al, 2022), empresas de turismo, hotelería y restaurantes (Goh et al, 2022;Lestari et al, 2021), en empresas de aviación (Divekar y Sukhari, 2021), empresas de comercio al por mayor y por menor (Buele et al, 2021), empresas de la industria automovilística (Swalih et al, 2021), empresas del sector inmobiliario de la India (Sidhu y Katoch, 2019), en las micro, pequeñas y medianas empresas en India (Prakash y Verma, 2019), empresas multidisciplinaria de Vietnam (Tung y Phung, 2019), empresas manufactureras (Siwi et al, 2018), entre otros.…”
Section: Revisión De Literaturaunclassified